Impact of Pharmacokinetic Modification of Controlled Release Floating Tablets of Ranolazine - B. S. Venkateswaralu (Journal of Global Pharma Technology, 2019)
The present study outlines a systematic approach for design and development of oral controlled release floating tablet formulation of Ranolazine. Floating tablet Ranolazine have been shown controlled release there by proper duration of action at a particular site and are designed to prolong the gastric residence time after oral administration. Effervescence and swelling properties were attributed on the developed tablets by sodium bicarbonate, Eutragit L 100 and HPMC Polymer combination, respectively. Five batches of tablets were prepared by the direct compression method. The physicochemical properties of different formulations, their Buoyancy lag time and total floating time and swelling index were evaluated. It was found that the hardness of the tablets were effects the Buoyancy characteristic of the dosage form. All five formulations possessed good floating properties with total floating time between 8 – 10 hrs. The in vitro release studies indicated that the floating dosage forms containing Eutragit L 100showed slower release. The cumulative % of in vitro drug release of formulation FR1, FR2, FR3, FR4, and FR5 were 49.36%,58.98%,72.22%, 98.88% and 76.89. Drug release to be enhanced by formulation F4 in compared with the marketed product. Accelerated stability study revealed that optimized formulation was stable for one month without any major changes in assay, dissolution profile, floating lag time and other physical properties. Based on best fitting method, optimized formulation was found to follow Higuchi Model release kinetic.